Beyond access: Islamic financial literacy and women’s empowerment - Sukoco, Bambang; Utami, Cahyaning Budi; Ivantri, Madha Adi; Awdalkrem, Alhussain (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This study examines the effect of Islamic financial literacy on women’s empowerment using Islamic financial inclusion as a mediating variable. In addition, digital financial literacy was examined to capture its complementary role in expanding women’s financial participation.Methodology – Using data of 140 female who were or had been married, this group reflects household decision-making roles and provides valuable insights into women’s empowerment. The relationships among the variables were analyzed using structural equation modeling-partial least squares (SEM-PLS). Findings – The results show that both Islamic financial literacy and digital financial literacy significantly enhance Islamic financial inclusion and women’s empowerment. However, Islamic financial inclusion does not significantly mediate the relationship between literacy (Islamic and digital) and women’s empowerment. Implications – The findings emphasize the need to strengthen financial literacy programs, both digital and Islamic, as part of broader efforts to advance women's empowerment in OIC (Organization of Islamic Cooperation) member countries. Financial institutions and policymakers should integrate literacy initiatives with inclusion strategies to ensure that women fully benefit from Sharia-compliant financial services.Originality – This study provides new evidence linking Islamic financial literacy, digital financial literacy, and Islamic financial inclusion to explain women’s empowerment. This offers insights into the pathways through which literacy and inclusion interact, particularly in the context of Islamic finance.